READING COMPREHENSION AND SELF-REGULATED LEARNING: A CROSS SECTIONAL STUDY OF UNIVERSITY STUDENTS - Sutiono, Cayandrawati; Triana, Novita; Arapah, Elvina (Universitas Muhammadiyah Metro, 2022)
Reading is a critical component of academic life. Undergraduate students' course success depends much on how they process their reading. However, some studies show that students face difficulties in their reading in several terms. These difficulties are twofold for English as a Foreign Language students who have to deal with reading and language content. In this respect, students must be able to self-regulate their reading activities in and outside classrooms. This study was intended to investigate the students' levels of self-regulated learning in reading comprehension. This study used a cross-sectional design with 40 English Language Education Study Program students at Universitas Lambung Mangkurat. The instrument was a questionnaire adapted from Zimmerman's Academic Self-Regulated Learning Scale (2000). The questionnaire was distributed online to the students using Microsoft Forms. The data were analyzed using a t-test. The findings show that the ways both groups of students regulate their cognitive processes, motivation, and behavior within an educational setting are similar. Nevertheless, concerning that the fourth-semester students might be more organized SRL students than the second-semester ones, reading instructions must be structured to develop students' self-regulated learning. In other words, lecturers should condition the instructions to enhance the students' self-regulation